The effect of different rates of selenium on grain Se concentration and yield of MR219 rice (Oryza sativa L.) - Alifar, Nafiseh; Abdul Rahman, Zaharah; Ishak, Che Fauziah; Awang, Yahya; Khayyambashi, B. (IEEE, 2012)
Selenium (Se) is one of the important micronutrient for human and animal. There is a relationship between the level of selenium in food system and the levels of plant-available Selenium in soil. This study was carried out on rice to observe the effects of addition of different Selenium rates on yield and Se concentration in rice. A filed trial carried out with five different Selenium rates did not show significant effects on MR219 rice variety yield, grain Selenium concentration and soil Selenium concentration.